Pelatihan Pembelajaran Berdiferensiasi Menggunakan Strategi Know_Want to Know_Learned Bagi Guru Sekolah Menengah Atas Arrohmah Malang - Siti Mafulah; Umi Tursini; Eufrasia Tika (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Differentiated learning is very necessary to facilitate students to obtain equal rights in classroom learning. With various backgrounds ranging from learning styles and learning methods of students and student categories (audio, visual, and kinesthetic), teachers are expected to be able to teach creatively and innovatively. However, not all teachers understand this, therefore it is necessary to conduct differentiated learning training using the Know, Want to know, and Learned (KWL) strategy so that teachers do not feel lectured in delivering their materials. This activity used 4 stages of implementation, the first stage K (Know), teachers were asked to write down what they know about differentiated learning, the second stage W (Want to know), what teachers wanted to learn related to differentiated learning, the third stage was the presentation of the material and the fourth stage L (learned), at this final stage, participants were asked to write down what they have learned from the presentation of the material and the discussions that have been carried out together. The results of the questionnaire stated that almost all participants felt happy and enthusiastic about participating in this activity and would apply differentiated learning in their respective classes.